2004
DOI: 10.7326/0003-4819-141-12-200412210-00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality of Care for Patients in the Veterans Health Administration and Patients in a National Sample

Abstract: Patients from the VHA received higher-quality care according to a broad measure. Differences were greatest in areas where the VHA has established performance measures and actively monitors performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
318
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 453 publications
(332 citation statements)
references
References 29 publications
10
318
3
1
Order By: Relevance
“…We believe this is the first study to examine evidence-based quality indicators in US veterans with gout diagnosis and to examine the physician characteristics as predictors of quality of gout care. These estimates likely understate the problem for the US as a whole, because recent studies demonstrate that the VA outperforms other systems in chronic disease management (9,23). These results confirm the findings by MacLean et al (8) of gaps in care quality for patients with rheumatic diseases, and extend their findings to include patients with gout.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe this is the first study to examine evidence-based quality indicators in US veterans with gout diagnosis and to examine the physician characteristics as predictors of quality of gout care. These estimates likely understate the problem for the US as a whole, because recent studies demonstrate that the VA outperforms other systems in chronic disease management (9,23). These results confirm the findings by MacLean et al (8) of gaps in care quality for patients with rheumatic diseases, and extend their findings to include patients with gout.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that quality of gout care is much worse in VA than non-VA settings, because many studies have found better quality care for patients in the veteran health administration than patients in a national sample (9) or those covered by Medicare (23). Nonetheless, studies of physician adherence to gout QIs in the general US population are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet performance measurement is itself an intervention, sometimes with unintentional and unforeseen consequences. 2,3 For example, the Veterans Health Administration (VHA) has long had a reputation as a leader in innovative clinical performance measurement, 4 yet perverse performance incentives around performance on access-to-care measures may have exacerbated the VHA's recent crisis of confidence. 5 Even before that crisis, the VHA organized a state-of-the-art conference (SOTA) featuring thought leaders of national prominence to set goals for the next generation of clinical performance measures.…”
mentioning
confidence: 99%
“…For example, in 2004 a RAND Corporation study measured the quality of medical care using a chart-based quality instrument consisting of 348 indicators. The study found that the VHA had substantially better quality of care than did a national sample [1]. Similarly, a 2009 Congressional Budget Office report [2] found that ''the care provided to VHA patients compares favorably with that provided to non-VHA patients in terms of compliance with widely recognized clinical guidelinesparticularly those that the VHA has emphasized in its internal performance measurement system.''…”
mentioning
confidence: 96%